Cross-border Education: Students Exchange Programme Participants’ Perspective on ERASMUS - S. Yu. Pavlina (Высшее образование в России)
Modern educational landscape has been undergoing drastic changes due to the processes of internationalization and transnationalization. Internationalization in higher education is manifold, student academic mobility being one of its manifestations. It is often associated with ERASMUS, the programme that has been implemented in European higher education for almost 30 years. It provides short-term student exchange programmes and involves EU member states as well as other European countries, including Russia. The effect of ERASMUS on higher education of EU countries has been thoroughly studied, while its Russian segment remains a white spot. This article reports on the study done among Russian students who participated in ERASMUS students exchange programmes in 2018–2020 as well as the Russian students educated along with their international colleagues in a home university. The employment of qualitative methods revealed that Russian participants of ERASMUS exchange programmes find them very effective. The most significant benefits include the development of cross-cultural competence as well as professional skills and personal growth. Students working with international participants of ERASMUS programme in a home university were very positive about the experience. Such communication makes the classes interesting, helps Russian students develop understanding of cultural issues, increases their motivation and gives impetus to self-development.